Microalbuminuria in Preeclampsia - Şen Özyer, Şebnem; Tapısız, Ömer; Güngör, Emre Sinan; Möröy, Perran; Mollamahmutoğlu, Leyla; Danışman, Nuri (Gynecology Obstetrics & Reproductive Medicine, 2006)
OBJECTIVE: The aim of this study is to assess the value of microalbuminuria in the diagnosis of preeclampsia, to compare the urinary albumin secretion rate between the high risk hypertensive patients and normal pregnant subjects and to find the relationship between microalbuminuria and pregnancy outcome. STUDY DESIGN: The study consisted of 40 normotensive women (control group) and 50 women in whom pregnancy was complicated by preeclampsia (study group). Liver and renal function parameters, bleeding profile, urinary microalbumin secretion rates and blood pressures were assessed. Student’s t test, Mann-Whitney U test and Spearman’s correlation analysis were used as statistical methods. A p value less than 0.05 was considered significant. RESULTS: Mean urinary microalbumin secretion rate was significantly higher in the study group than in controls (481.54±36.36 mg/lt v s 69.13±15.92 mg/lt). Platelets, liver function parameters and serum creatinine levels did not show any significant difference between groups (p>0.05). We found no correlation among microalbuminuria, blood pressure and fetal outcome (p>0.05). CONCLUSIONS: Microalbuminuria may be used in the diagnosis of preeclampsia. We found no correlation with pregnancy outcome.